Chromogenic, Biochemical and Proteomic Identification of Yeast and Yeast-like Microorganisms Isolated from Clinical Samples from Animals of Costa Rica - Calderón Hernández, Alejandra (2024)
Yeast infections are challenging human and animal medicine due to low rates of detection and the emergence of unknown ecology isolates. The aim of this study was to verify the biochemical identification of yeasts and yeast-like microorganisms obtained from animals comparing the results with chromogenic media and matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF MS). Between January and August 2023, yeast and yeast-like isolates from samples of animals with suspicion of mycosis were identified using Vitek® 2 Compact, Brilliance® Candida Agar and MALDI Biotyper® MSP. A total of 39 cases were included, and 45 isolations were obtained. Cryptococcus neoformans (15.5%, 7/45), Meyerozyma guilliermondii (13.3%, 6/45), Candida parapsilosis (11.1%, 5/45), Candida albicans and Candida tropicalis (8.9%, each one 4/45) were the most identified organisms. There was full agreement with the three identification methods in 71.1% (32/45) of the isolates, disagreement on species in 17.8% (8/45), disagreement on genus and species in 6.7% (3/45) and, in 4.4% (2/45), there was no matched pattern in MALDI-TOF to compare the results. Biochemical methods are a good option in laboratories where proteomics are not available, and chromogenic media enhances diagnostics by detecting mixed infections. Surveillance must be implemented to improve the detection of agents shared between humans and animals.